STUDI KOMPARASI PENGGUNAAN MULTIMEDIA POWERPOINT DAN VIDEO ANIMASI DALAM MENINGKATKAN PEMAHAMAN KONSEP BILANGAN BULAT PADA SISWA SMP - Rahmansyah, Bagus; Warli, Warli (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
This study aims to compare the use of PowerPoint multimedia and video animation in improving the understanding of integer concepts in junior high school students. The use of interactive multimedia is an important part of education today, but the use of multimedia is still limited when teaching in the classroom. In this research, an experiment was carried out involving two groups of junior high school students. The first group used animated videos while the second group used PowerPoint multimedia. The data collected includes tests of understanding the concept of integers before and after using PowerPoint multimedia and animated videos in teaching. The analysis used includes the normality test, homogeneity test, and t-test to test whether there is a difference or not from the data of each group. The results of the data analysis show that there are differences in understanding the concept of concept numbers between those using powerpoint media and animated videos. The group that experienced the most significant difference was the group that used video animation compared to the group that used PowerPoint multimedia. The use of animated videos in this context can be an effective and interesting alternative in learning the context of integers.